The Influence of Prostaglandin E1 and Use of Inhibitor Percentage on the Correlation between the Multiplate and VerifyNow in Patients on Dual Antiplatelet Therapy. (19th May 2021) - Hulshof, Anne-Marije; Vries, Minka; Verhezen, Paul; Wetzels, Rick; Haartmans, Mirella; Olie, Renske; Ten Cate, Hugo; Henskens, Yvonne
Abstract: Platelet function tests (PFT), such as the Multiple Electrode Analyzer (Multiplate) and VerifyNow, show little concordance in patients using antiplatelet drugs. A major difference between these tests is the use of prostaglandin E1 (PGE1) to inhibit P2Y1-platelet-receptor activation in VerifyNow and is proposed to be of influence in the discrepancy between these tests. We aimed to investigate whether the presence of PGE1 could provide an explanation for the moderate correlation and concordance between Multiplate and VerifyNow by adding PGE1 to the Multiplate ADP assay, also known as the ADP-high sensitivity (ADP-HS) assay. We also aimed to investigate whether the difference in baseline platelet function as measured by the VerifyNow and Multiplate could (partly) explain the moderate correlation between the tests, by plotting ADP assay results against baseline function as measured by the corresponding device, which is expressed as the 'inhibitor percentage.' Fifty-one patients who underwent percutaneous coronary intervention (PCI) received dual antiplatelet therapy and were considered to have a high risk of ischemic or bleeding complications were included. The addition of 20 µl PGE1 in the Multiplate resulted in a significant reduction in Arbitrary Aggregation Units, but did not improve correlation with the VerifyNow. The correlation between VerifyNow and Multiplate inhibitor percentage was moderate. Based on these results, we concluded that neither PGE1 nor the calculation of the inhibitor percentage greatly influenced the correlation between PFTs.